Sol – Jel Yöntemi İle Hazırlanan Tio2 – Sio2 Nanokompozit İnce Filmlerin Fiziksel Ve Mekanik Özelliklerinin İncelenmesi - Biçer, Ezgi Deniz (Fen Bilimleri Enstitüsü, 2015)
Cam ve cam ürünleri geniş kullanım alanına sahip olduğundan günlük hayatımızda önemli ölçüde yer almaktadır. Kuşkusuz, saydam ve inert bir malzeme olan cam, aynı özelliklere sahip diğer malzemelerden üstündür. Amorf yapısı nedeniyle kırılgan ve mekanik mukavemet değeri düşük olan camın, teorik mukavemet değeri ise oldukça yüksektir. Teorik ve pratik mukavemet değeri arasındaki fark, 1921 yılında Griffith tarafından ortaya atılan teoriye göre; mikro çatlak olarak tanımlanan yüzey kusurlarından kaynaklanmaktadır. Griffith’in varsayımından günümüze, bu hataların yok edilmesi veya etkilerinin azaltılması yönünde birçok çalışma literatürde yer almaktadır. Mukavemet, malzemelerde en önemli mekaniksel özelliklerden biri olup kullanım amacına uygunluğu belirleyen temel unsurdur. Mukavemet artışıyla birlikte, camın kullanım alanlarının genişletilmesi, kalınlığının azaltılarak hammadde sarfiyatının ve üretilen ürünlerin ağırlığının düşürülmesi gibi avantajlar elde edilebilir. Daha az hammadde tüketimi, yüksek teknolojik malzemelerin üretiminde daha çevreci çözümler sunar. Mukavemet arttırma amacıyla uygulanan birçok başarılı teknik mevcut olmasına rağmen, boyut ve şekil sınırlaması olmayan, çevreye duyarlı, enerji, zaman ve maliyet tasarrufu sağlayan tekniklerin ve alternatif yöntemlerin geliştirilmesi güncelliğini korumaktadır. Cam yüzeyinin ince film tabakası ile kaplanması bu yöntemlerin başında gelir. Son yıllarda yaş kaplama yöntemlerinden sol-jel yöntemi, büyük ölçekli yüzeylerin ekonomik, hızlı ve kolay şekilde kaplanabilmesi nedeniyle tercih edilmektedir. Mukavemet arttırma çalışmaları yapılırken, camın saydamlığından ödün vermemek amacıyla optik özelliklerin değişmemesi ön plandadır.  Kaplamanın cam yüzeyine iyi bir şekilde tutunması, çizilmeye karşı dayanıklı olması da kaplamanın cam ile birlikte kullanım ömrünü belirleyen ölçütlerdir. Bu çalışmada, cama mukavemet artışı sağlayan ve cam ile benzer optik özellikler gösteren, çizilmeye dayanıklı, yüzeye iyi bir şekilde tutunan kaplamaların geliştirilmesi hedeflenmiştir.  Deneysel çalışmalar kapsamında, TiO2 – SiO2 nanokompozit kaplama çözeltisi hazırlanmış ve DTA-TG analizi yapılarak kaplamalar için optimum kürleştirme şartları belirlenmiştir. Kaplamaların farklı kalınlıktaki camların mukavemetinde yaratacağı etkinin belirlenebilmesi amacıyla ŞİŞECAM Trakya Fabrikası tarafından üretilen camlardan en ince olan 1,6 mm ve 2,2 mm kalınlıktaki camlar temin edilmiştir. Camlar, iki ayrı set halinde; kontrollu çentik bırakıldıktan sonra (300 gram yük altında 5 saniye) ve çentik bırakılmadan (Fabrika’dan geldiği gibi) hazırlanmıştır. Tüm cam altlıklar, Daldırarak kaplama tekniğiyle üç farklı çekiş hızında (10 mm/dk, 50 mm/dk ve 150 mm/dk) tek kat kaplanarak, 190°C sıcaklıkta 5 dakika süresince ısıl işlemden geçmiştir.  Kaplama yüzeyleri,  SEM-EDS, Temas açısı ve Serbest Yüzey enerjisi ölçümleriyle karakterize edilmiştir. Farklı çekiş hızı ile yapılan kaplamaların kalınlıkları hem SEM yan kesit görüntüsü hem de Profilometre ölçümleri ile belirlenmiştir. Kaplanmamış ve farklı çekiş hızları ile kaplanmış camların mukavemet değerleri halka üstü halka (ROR) düzeneği ile test edilmiştir. Elde edilen sonuçlar ve sonuçların güvenirliği Weibull istatistiksel dağılımları ile tartışılmıştır. Çentik bırakılıp kaplanan 1,6 mm ve 2,2 mm camların her iki setinde de yaklaşık ortalama %230 mukavemet artışı tespit edilmiştir, Çentik bırakılmamış her iki sette ise, yaklaşık %150 mukavet artışı olmuştur. En yüksek çekiş hızı ile kaplanan 2,2 mm cam setinde kırılmayan örnekler bulunduğundan, bu sette minimum %330 mukavemet artışı olduğu söylenebilir.  Spektrofotometre ile örneklerin geçirgenlik ve yansıtma değerleri ölçülerek karşılaştırılmış ve kaplamaların cam kadar saydam olmasının yanında camdan daha geçirgen olduğu belirlenmiştir. Kaplamalara, fiziksel testler uygulanmış, ASTM standartlarına göre, yüzey tutunma, çizilme ve kalem sertlik testleri yapılmış ve kaplamaların cama çok iyi bir şekilde tutunduğu ve sertliklerinin maksimum kalem sertlik (9H) değerlerinde çıktığı tespit edilmiştir. Bununla birlikte, kaplamaların mikro-nano ölçekte mekanik karakterizasyonunu değerlendirebilmek için Nano mekanik test cihazı ile Berkovich elmas indentasyon ucu kullanılarak, nano indentasyon deneyleri yapılmış, hazırlanan kaplamaların ve elde edilen ürünün Nanosertlik, Vickers sertliği ve Elastik modülü değerleri elde edilmiştir.

Glass and product of glass is widely used in our daily life. The glass is a, unique and qualified of being transparent and inert material and distinguished between any other materials which has the same properties. Fragile, because of its amorphous structure, has non-crystalline characteristics because of cooling quickly from its liquid phase to solid phase. It has low mechanical resistance but, calculated value of the mechanical resistance values are very high, the measured mechanical resistance values are only 1-4% of its theoretical value. The reason of this dramatical difference between theoretical and practical strength is defects at surface and just below the surface called microcracks. This theory suggested by Griffith in 1921.  From the Griffith's theory, the microcracks are originate as a result of variable conditions at manufacturing process, like sudden temperature fluctuations in melting furnace, pressure changes, or different composition of raw materials, contamination because of air pollution. From Griffith's suggestion of the mechanical strength of glass can be improved by removing surface defects, cracks or by creating a counter stress which will prevent the growth of the cracks at glass surfaces. In the past, there are many works about eliminate of these defects or decrease the effects of them. Mechanical strength is quite important feature for materials to decide suitability at any application area. Mechanical properties affect all design parameters. Therefore, it is important to know or predict behavior of materials before using them in any system. Improving the mechanical properties and increasing the mechanical strength of the glass is, bring about many advantages like, getting utilization field wider, obtaining lightweight products, and decreasing the amount of raw materials used at manufacturing process.  With the development of the technology the need for lighter and stronger materials has become more important. There are many successful techniques for increasing the mechanical strength of the glass but, alternative methods are always preferable because of its advantages like, no limiting at size or shape, sensitive to the environment, providing energy, time, cost and raw material saving. One of the alternative method is thin film coatings. Thin film technology have been studied extensively because of its ease of use. It consumes less material, thus it is more environmental solution for fabrication of advanced materials. Ultimate strength, wear resistance and chemical resistance are some features that can improved by thin film technology.  Coating techniques should be inexpensive and compatible with batch processes. Sol-Gel coatings is the most preferable one because of its benefits like easy application ways and being economical to coat extensive surfaces. Sol-gel process offers an efficient platform to scientists to coat the glass, because of numerous reasons: it requires relatively simpler laboratory equipment and offers a large portfolio of starting materials and lastly. Moreover, it allows modification of surfaces quite effortlessly. Having mechanically strengthened samples and same optical properties, to not give up from transparency at the same time is possible with Sol-Gel coatings.  Quality of the coating related to good adhesion of the coating to the surface and, durability in front of scratch. In brief, the targeted result is not only mechanically strengthened glass in addition to have same or has better optical properties than uncoated glass and durable against scratch, highly qualified coated glass. It is possible with sol-gel thin film coatings to gain attribute more than one. The choice of the material is very important. Toxicity is the biggest problem for various usages. Titanium and its oxide forms are quite popular materials because of their compatibility with human body. The main reason is the chemical inertness of this material. Titanium used for surgeries since 1950s and it is not affected by body fluids. Besides, it withstands external forces very well. TiO2  - SiO2 thin film coatings which are prepared by sol gel method had been decided as research topic, as for its ease of application, lower prices and for its modification advantages.  The surface of the flat glass samples coated with nanocomposite coating solution, using dip coating technique. The purpose of this work is increasing the mechanical strength and improve other mechanical properties of the glass  while the optical properties of the glass remains the same. As a result of research, using TiO2 – SiO2 nanocomposite thin films prepared by sol-gel process was deemed appropriate. Water based, including TiO2 – SiO2 coating solution prepared and flat glass substrates coated single layer with dip coating technique, by various withdrawal speed; 10 mm/min, 50 mm/min and, 150 mm/min then coatings exposed to heat treatment at 190°C for 5 minute. Dip coated flat glass substrates which has two different thickness 1,6 mm and 2,2 mm. The substrates indented with Vickers indenter by under 300 gram for 5 seconds then coated to investigate success of coating solution to fill cracks and improvement at mechanical strength. At the first part of the study, is introduction and, at the second part is including general informations about thin films, sol-gel method, its advantages and disadvantages and its application field, then thin film optics, nanoindentation and obtained properties with using nanoindentation experiment, glass materials, strength, glasses theoretical strength, ways to increase glass strength and Weibull statistical distribution. The third part is expressing the materials and methods which are used during the work, like supply flat glass substrates, cleaning procedure of the glass surfaces, indentation at glass surface, preparation of coating solutions, coating method and technique, characterization methods, DTA-TGA, EDX, contact angle and surface energy, measurement of coating thickness, measurement of optical properties, physical tests, ring on ring mechanical tests, surface adhesion tests, scratch tests, pencil scratch tests and nanoindentation and nanohardness tests.  Heat treatment of the samples was decided after a DT analysis. Ring on ring mechanical test system applied at uncoated samples and coated samples with different withdrawal speed to calculate mechanical strength of the samples. The resutlt of mechanical strength of the samples were compared with each other. The coating increased the mechanical strength value for two times. Samples mechanical strength values analyzed with using of a Weibull statistical analyses.  For characterizing the coating surface, contact angle measurement dataset are compared for uncoated and coated samples. Then contact angles with pure water and Ethylene Glycol are measured and used for calculating the surface energy.  The thickness of the coating measured to use for nano mechanical tests. The optical properties of glass is measured with spectrophotometer. Transmittance and reflectance of uncoated and coated glass were measured, then the results compared, there were no significant changes at reflectance and transmittance value between the coated samples and, the coated samples have nearly the same transmittance and reflectance value with uncoated samples. The optical properties did not effected with thickness of film or with film. The coated samples as transparent as uncoated glass samples. The physical tests applied on the test samples to get information about quality of the films, from the result of these tests, the film layer has nearly 100% durability against pencil hardness test and has excellent adhesion at glass surface by considering the related ASTM standards.  Nanomechanical tester and Berkovich diamond indenter used for nanoindentation test experiments, nanohardness, Vickers hardness and elastic modulus values measured for films and for the product obtained. The results compared with uncoated glass' results.
Investigation Of Physical And Mechanical Properties Of Tio2 - Sio2 Nanocomposite Thin Films Prepared By Sol – Gel Method
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Cam Mukavemeti; Mekanik Özellikler; Nanoindentasyon; Sol-jel; Glass Strength; Mechanical Properties; Nanoindentation; Sol-gel